Dukungan Manajemen dalam Peningkatan Kepemimpinan Klinis Perawat Pelaksana - Patricia Olivine Aprilis Hutapea; Sontina Saragih (An-Najat, 2023)
Clinical leadership is a combination of knowledge, skills and abilities in implementing changes for better nursing services. Nurses with clinical leadership that are not yet optimal display knowledge, abilities and characteristics that are inappropriate in a quality nursing service system. Management support is one of the factors that can stimulate the development of clinical leadership for nurses in providing nursing care. This study aims to analyze management support in improving the clinical leadership of implementing nurses. This research design is quantitative with a croo-sectional study approach to 151 nurses at Bunda Thamrin Public Hospital using a random sampling technique. Data on management support and clinical leadership of nurses were analyzed using SPSS version 16 and the results are presented in the form of tables and statements. Correlation test was conducted to identify the relationship between management support and the clinical leadership of the implementing nurses. The results showed that almost all of the practicing nurses were in early adulthood, most of the practicing nurses were female, almost all of the practicing nurses were with vocational education levels and most of the respondents had long working years and there was a significant relationship between management support and clinical leadership abilities, with p-value of 0.000. The conclusion of the research results is that management support can improve clinical leadership of nurses. Because of this, it is hoped that the management of Bunda Thamrin General Hospital can provide opportunities for nurses to attend seminars or trainings, especially related to clinical leadership skills to obtain quality nursing services.